Teachers’ Strategies for Improving ESL Learners’ Speaking Skills - Aryal, Muna (Journal of NELTA Koshi (JoNK), 2024)
The study examines the perception of Nepalese English teachers on the strategies employed to enhance ESL learners’ speaking skills. To gather insights and experiences, interviews were conducted with two secondary-level English teachers from schools in the Kathmandu valley. The findings reveals that creating a supporting learning environment and utilizing different teaching strategies, such as task-based learning and communicative language teaching are crucial for improving students’ speaking abilities. The study also highlights how socio-economic and cultural factors influence language learning, underscoring the need for the inclusive and equitable educational practices. Despite the study’s contributions to understanding effective ESL teaching practices and its practical implications for educators and policymaker, effective reading strategies are underestimated. The study emphasizes the importance of adopting effective teaching strategies and fostering supportive learning environments to enhance ESL learners’ speaking skills and confidence in using English.